2004
DOI: 10.1128/aac.48.9.3279-3283.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Caspofungin Combined with Sulfamethoxazole against Clinical Isolates of Aspergillus spp

Abstract: Caspofungin (CAS) inhibits fungal cell wall synthesis. Sulfamethoxazole (SMX) inhibits folate biosynthesis and is active in vitro against Aspergillus spp. We studied the activities of the combination of CAS and SMX against 31 Aspergillus isolates and compared them with that of SMX combined with amphotericin B (AMB) or itraconazole (ITC). MICs and minimal effective concentrations (MECs) were determined by the NCCLS broth microdilution method. With MIC endpoints, the combination of SMX and CAS showed synergy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…in the presence of caspofungin (26,28,29). These studies, however, did not aim at a comprehensive description of the concentration-dependent effects of caspofungin on the metabolic activity of this organism, and consequently the number of isolates for which the assay was performed was limited (six isolates for all three studies).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the presence of caspofungin (26,28,29). These studies, however, did not aim at a comprehensive description of the concentration-dependent effects of caspofungin on the metabolic activity of this organism, and consequently the number of isolates for which the assay was performed was limited (six isolates for all three studies).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MEC is an endpoint that is based upon qualitative assessment of hyphal morphology and, as such, it does not provide quantification of caspofungin activity at different concentrations. For example, using the MEC as an endpoint may be problematic for in vitro antifungal combination studies, in which the detection of significant drug interactions may require the use of more sensitive, quantitative methods that could demonstrate a concentration-effect relationship for caspofungin activity against this organism (29). Thus, in order to better understand the in vitro activity of caspofungin against Aspergillus spp.…”
mentioning
confidence: 99%
“…In this study, we tried to perform the susceptibility tests with yeast nitrogen base, as suggested by Hanafy et al (2007), but unfortunately this medium did not support the growth of C. posadasii (data not shown). Because other studies have already been performed with RPMI (Yekutiel et al 2004, Navarro-Martinez et al 2006, we decided to evaluate this medium in our experiments. However, we assumed that in PABA-free medium, SMX/ TMP may cause a greater reduction in AMB MICs.…”
mentioning
confidence: 99%
“…Deletion of pabA , encoding PABA synthase, catalysing an early step in folate biosynthesis, abrogated virulence in infected mice, designating this pathway as an excellent candidate for the development of novel antifungals [33]. Antibacterial sulfa drugs that inhibit dihydropteroate synthase in the folic acid biosynthetic pathway already exist and show weak antifungal activity [34]. Recent efforts have focused on developing antifungals to target other enzymes in this pathway [35].…”
Section: Discussionmentioning
confidence: 99%